Primary Ewing's sarcoma of the occipital bone - Case report - Erol, FS; Ozveren, MF; Ozercan, IH; Topsakal, C; Akdemir, I (Japan Neurosurgical Soc, 2001)
A 17-year-old female presented with a very rare case of primary Ewing's sarcoma of the skull involving the occipitotemporal region. Systemic examination found no evidence of metastasis. The tumor was surgically removed, and the patient underwent radiotherapy and chemotherapy. Fourteen months after surgery there has been no recurrence of the tumor. Cranial primary Ewing's tumor has a good prognosis after radical surgery and adjuvant therapy.
Keywords: cranium; Ewing's sarcoma; occipital bone